Healing of the periapical lesion in posterior teeth with mineral trioxide aggregate using orthograde technique - Two case reports - Mohan L Paul; Dibyendu Mazumdar; Nishant K Vyavahare; Akash K Baranwal (Wolters Kluwer Medknow Publications, 2012)
Conventional root canal treatment (RCT) of the teeth has long shown high success rate. However, the endodontic treatment of a pulpless tooth with periapical radiolucency of a considerable size always has a question of success. In modern days, surgical exploration is avoided, especially in the posterior teeth. These types of cases may be successfully managed by orthograde Mineral Trioxide Aggregate (MTA) placement in the apical third of the root followed by proper obturation. The objective of our present case reports was to evaluate the periapical pathology of posterior teeth clinically and radiographically by using MTA in orthograde way and avoiding traumatic surgical exploration. In the first case, the patient reported with intraoral sinus and pus discharge related to tooth #45. On radiograph, open apex (blunderbuss) was found along with periapical radiolucency. In the second case, the patient reported with pain and swelling related to tooth #26, having large periapical radiolucency related to the palatal canal. On vitality test, both the teeth responded negative, i.e., non-vital. Conventional RCT was planned in both the cases with orthograde MTA- Angelus (Angelus, Londrina, PR, Brazil) apical plug followed by the proper obturation with gutta-percha (G.P.), and after that the patients were kept on periodic follow-up and the outcome-based clinical and radiographic criteria were assessed. The post-obturation assessment at 1-month interval showed changes in the size of radiolucency with a gradual decrease, and after 6 months a remarkable decrease of radiolucency or the defect was almost filled with bone formation visible around the roots.